Private Property and Protection of Private Property - The Foundation of A Sustainable Development Environment - Duy, Nguyen Dang (VNU Journal of Science: Legal Studies, 2020)
Property ownership is an ancient concept and plays an important role in determining the status of each individual in society and for the nation's development. During the past 70 years since its inception, the Democratic Republic of Vietnam, which is the Socialist Republic of Vietnam today, has only policy guidelines for this guarantee. Keywords: property ownership, private economic, private ownership. References: [1] Melvin Urofsky, Rights of The People: Individual Freedom and The Bill of Rights. [2] Garrett Hardin, The tragedy of the commons, Science 162 (3859) 1968. [3] Milton Friedmen and Rose Friedman, Capitalism and Freedom, University of Chicago, IL., 1962. [4] Nguyen Huy Vien, Developing private economy, the people will be richer and the country will be stronger, 22/05/2019. https://vietnamnet.vn/vn/tuanvietnam/tieudiem/chi-khi-kinh-te-tu-nhan-phat-trien-moi-co-dan-giau-nuoc-manh-533536.html. [5] Karl Marx, The Communist Manifesto, 1848, London. [6] Pham Thi Thanh Binh, Private economy: An important driving force in Vietnam's economic development, tapchitaichinh.vn 13/01/2018. http://tapchitaichinh.vn/nghien-cuu--trao-doi/trao-doi-binh-luan/kinh-te-tu-nhan-dong-luc-quan-trong-trong-phat-trien-kinh-te-viet-nam-134456.html. [7] Le Tho Binh, “The king of tires” Nguyen Van Chan: a… miser, Vietnamnet.vn 11/10/2004. https://vietnamnet.vn/psks/nhanvat/2004/10/333737/.